Islamic Cultural Values among Malaysian Muslim Accountants and Their Influence on Corporate Social Accountability - Alazzabi, Mohamed Salem Issa (2009)
This study investigates the influence of Islamic culture on corporate social accountability among Muslim accountants in Malaysia. Two independent variables are proposed namely collectivism and power distance. Multivariate analysis was employed to examine the relationship between variables in the framework and 40 respondents involve in this study. It is found that there is no relationship between collectivism and corporate social accountability. On other hand there is a significant positive relationship between power distance and corporate social accountability. In conclusion this study recommends the need to integrate Islamic values in accounting practice. Encouraging Islamic-driven accounting practice can improve financial disclosure and in turn decision making.